2005
DOI: 10.1074/jbc.m411734200
|View full text |Cite
|
Sign up to set email alerts
|

TSG-6 Protein Binding to Glycosaminoglycans

Abstract: TSG-6 protein, up-regulated in inflammatory lesions and in the ovary during ovulation, shows anti-inflammatory activity and plays an essential role in female fertility. Studies in murine models of acute inflammation and experimental arthritis demonstrated that TSG-6 has a strong anti-inflammatory and chondroprotective effect. TSG-6 protein is composed of the N-terminal link module that binds hyaluronan and a C-terminal CUB domain, present in a variety of proteins. Interactions between the isolated link module … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 59 publications
2
27
0
Order By: Relevance
“…carried out in the solution state) showed that the affinities of Link_TSG6 for HA 8 AN and HA 20 AN are higher at pH 6.0 than at pH 7.4 (ϳ2.5-and 7-fold, respectively). These data reaffirmed our previous findings on the pH dependence of the Link_TSG6-HA interaction (22) but appear to be inconsistent with the results of a recent study (35). However, it should be noted that Wisniewski et al (35) examined the binding of TSG-6 to immobilized HA in the presence of 0.5 M NaCl (i.e.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…carried out in the solution state) showed that the affinities of Link_TSG6 for HA 8 AN and HA 20 AN are higher at pH 6.0 than at pH 7.4 (ϳ2.5-and 7-fold, respectively). These data reaffirmed our previous findings on the pH dependence of the Link_TSG6-HA interaction (22) but appear to be inconsistent with the results of a recent study (35). However, it should be noted that Wisniewski et al (35) examined the binding of TSG-6 to immobilized HA in the presence of 0.5 M NaCl (i.e.…”
Section: Discussionsupporting
confidence: 66%
“…In marked contrast, the pH dependences of both Link protein and the G1 domain of aggrecan (two constitutively expressed HA-binding proteins) for HA have no drop in affinity between pH 6.0 and 8.0 (22). Recently, the pH dependence of the HA-Link_TSG6 interaction has been questioned (35), with suggestions that the earlier observation results from an artifact of the solid-phase assays used (i.e. where either the protein or HA was immobilized on the surface of the microtiter plate).…”
mentioning
confidence: 99%
“…This unusual pH dependence appeared to be in marked contrast to that for the G1 domain of aggrecan, where the highest affinity was reported at neutral pH 7.0 -8.0 (31). However, it has been suggested that the unusual pH dependence we reported for the HA-Link_TSG6 interaction may have resulted from an artifact of the solid phase assay used in the analysis (32). In recent work, isothermal titration calorimetry (ITC) was used to show that the Link_TSG6 had a higher affinity at pH 6.0 compared with pH 7.5 for short oligosaccharides of HA in solution phase and a structural basis for the pH dependence was identified using a combination of site-directed mutagenesis, NMR and ITC (33).…”
mentioning
confidence: 85%
“…Therefore, it seems likely that HA 10 is the minimum length of HA able to occupy the HA-binding site on G1, but that HA 12 has slightly tighter binding. Earlier estimates of the footprint of aggrecan on HA suggested that at maximal packing density it occupied a longer stretch of HA (ϳHA 18 ) than was part of the minimal binding site (31) and more recent experiments comparing the binding of recombinant G1 to HA 32 and HA 40 also suggested a longer site occupied, which may result from negative cooperativity (13). Alternatively, this may be caused by the spatial constraints of how close G1 domains (which each have 2 Link modules and an Ig fold) can pack when bound to HA.…”
Section: Effect Of Ph On the Binding Of The G1 Domain Of Aggrecan Withmentioning
confidence: 99%
“…The 35-kDa protein is composed of a link and a CUB domain. The link domain mediates binding to glycosaminoglycans via two distinct binding sites (2,3). The CUB domain in TSG-6 is less studied, but it has been shown recently that the domain mediates interaction with fibronectin (4).…”
mentioning
confidence: 99%